Pengaruh Aplikasi Pupuk Kandang dan Sistim Tanam terhadap Hasil Varietas Unggul Padi Gogo pada Lahan Kering Masam di Lampung - Junita Barus (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2012)
Barus, Y. 2012. The Effect of Manure Application and Planting System on the Production of Upland Rice Varieties on Dried Acid Land in Lampung. J. Lahan Suboptimal 1(1):102-106. Upland rice planted in the dry land is very potential to contribute to the national rice production since upland area is quite large and its cultivation does not require irrigation.. The research was aimed to observe the effect of planting system and the application of organic matter on the production of upland rice. The experiment was carried out in the Buyut Udik village, the Gunung Sugih Subdistrict, the Middle Lampung Regency during the first season 2008/2009. Using Split Plot Design which consisted of two factors, namely: A. Planting System (The tegel system (20 x 20 cm), The planting system legowo 2: 1, and The planting system legowo 4: 1); B. Cow manure(without manure, and with manure 4 t/ha). Inorganic fertilizers applied were Ponska 15:15:15 (200 kg/ha) and urea (200 kg/ha). The highest production of 4,52 t/ha was obtained from the treatment legowo 2:1 with manure 4 ton/ha, followed by the tiles system with manure (4,24 t/ha), and the lowest was obtained from the treatment legowo 4:1 without manure (3,55 t/ha).